Care, learning and leisure : the organisational identity of after-school centres for six-to nine-year old children in Reykjavík - Kolbrún Þ. Pálsdóttir 1971- (2012)
kolbrunp@hi.is The provision of out-of-school care for young school children is the fastest growing day-care service in Europe. This study investigates the role and organisational identity of after-school centres in Reykjavik, Iceland, from the perspectives of different stakeholders. The theoretical framework for the study was drawn from institutional theory, the theory of communities of practice and childhood studies. A qualitative, multi-case study design was used to investigate Reykjavík after-school centres and two different after-school centres in Reykjavik were chosen as subjects for detailed investigation. Research methods included interviews, observations, and an analysis of documents and drawings. Three main research questions were asked: (a) What is the purpose of the after-school centres in Reykjavik, and how has public policy reflected that purpose? (b) How do recreation personnel experience their role? (c) How do children view the daily activities in the after-school centre, and how do they experience the difference between their school and their after-school centre? This study reveals how unclear the rationale for the service is, as its justification has shifted between care, learning and leisure over the years. The main findings are threefold: (a) The institutional status of the service is weak. Furthermore, no specific legislation addresses the operation of the after-school centres. (b) The professional identity of the recreation personnel is unclear. The majority of the recreation personnel had no specific qualifications and made only short-term commitments to the work. However, the study shows that the leaders of the after-school centres assumed the principal responsibility for the work. (c) After-school centres provide an important opportunity for play and social activities, from the perspectives of the children. The children constructed their own communities of practice, within which they organised their social relationships, experiences of learning, and histories of knowledge, that were ...